2010
DOI: 10.1111/j.1759-1961.2010.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances of sleep perception in a group of multiple sclerosis patients: A case report

Abstract: Sleep misperception, whether severe enough to qualify as paradoxical insomnia or not, is common in a number of neurological and psychiatric conditions. The objective was to assess sleep perception in a group of multiple sclerosis (MS) patients. As part of an Institutional Review Board (IRB) approved trial designed to assess the efficacy of eszopiclone versus placebo in improving MS patients’ sleep continuity, we observed a pattern of both paradoxical and reverse paradoxical insomnia in a small number of partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Waking up too early has been described as a common problem of the MS patient [2, 13]. Although Attarian et al [23] observed misperception of sleep in MS patients, their subjective complaints of problems with falling asleep and awakenings during the night were confirmed by the results of the Multiple Sleep Latency Test [5], polysomnography [24] and actigraphy [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Waking up too early has been described as a common problem of the MS patient [2, 13]. Although Attarian et al [23] observed misperception of sleep in MS patients, their subjective complaints of problems with falling asleep and awakenings during the night were confirmed by the results of the Multiple Sleep Latency Test [5], polysomnography [24] and actigraphy [11]. …”
Section: Discussionmentioning
confidence: 99%